If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 15 = 3 + 8x + -8 Reorder the terms: 15 + 6x = 3 + 8x + -8 Reorder the terms: 15 + 6x = 3 + -8 + 8x Combine like terms: 3 + -8 = -5 15 + 6x = -5 + 8x Solving 15 + 6x = -5 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 15 + 6x + -8x = -5 + 8x + -8x Combine like terms: 6x + -8x = -2x 15 + -2x = -5 + 8x + -8x Combine like terms: 8x + -8x = 0 15 + -2x = -5 + 0 15 + -2x = -5 Add '-15' to each side of the equation. 15 + -15 + -2x = -5 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = -5 + -15 -2x = -5 + -15 Combine like terms: -5 + -15 = -20 -2x = -20 Divide each side by '-2'. x = 10 Simplifying x = 10
| 2+6xt=-9 | | 3x^2-5x+2=4x+2 | | b=a^3-(a-3) | | 4(x+1)/8=3x-2 | | p=2x^2+18x+332 | | 2A+4=16 | | 7x+25x^2+4=5+7x | | 2x+7(3x-13)=47 | | 9(X-1)+X=8(3-X)-6 | | 0.04+X=74.52 | | y+2=-6/5+6/5 | | 13+2r=3r+7 | | 3(5-x)=9(15x-5) | | x/8=54 | | 3.75+3y=6 | | f(x)=8-7(4x+2) | | 2x+9=1x+1 | | 6x+3(2x+2)=102 | | 31=x+2x+(3x+1) | | 2x^2-5x-12.5=0 | | 2x^2-5x-12.51=0 | | 5x+7y/3(x+y) | | -3x-4=-6-5x | | 3x+5(25-x)=89 | | 7x+12y=34 | | 2(x+2)=3(x+6) | | 7x+12y=86 | | 3x+5(25-5)=89 | | 4(X+1)-2=6(5-X)+3 | | -3-2(x+4)=25 | | ln(2x+6)=-10 | | f(x)=4-x^2+5x^2 |